THE ROLE OF INDEPENDENT LEARNING IN DEVELOPING READING SKILLS - Khalilova Shokhista Mukhammadi qizi; Pardayeva Bahora Yusupovna (TADQIQOTLAR, 2026)
Annotation This article examines the role of independent learning in developing students’ reading skills in the process of foreign language acquisition. Reading is considered one of the most important language skills that enables learners to gain information, improve vocabulary, and develop analytical thinking. The study analyzes modern independent learning strategies, learner autonomy, digital educational technologies, motivation, and self-assessment  methods  that  contribute  to  improving  reading  comprehension.  The article also discusses pedagogical and psychological aspects of independent learning and highlights the significance of innovative teaching methods in enhancing students’ reading competence.